Strategies for lowering milk carbon footprints in small-scale dairy farming: A Kenyan perspective - Gonzalez-Quintero, Ricardo; Dusingizimana, Petronille; Notenbaert, An (2024)
Kenya's dairy cattle sector accounts for approximately 15% of the country's total greenhouse gas emissions (GHGE), emphasising the critical need to endorse sustainable dairy production strategies to enhance productivity and ameliorate environmental performance. This study aims to assess milk carbon footprint (CF) reductions through an ex-ante evaluation of mitigation interventions scenarios for 96 dairy farms in Kenya using a "cradle to farm-gate" Life Cycle Assessment approach. Global warming potentials for a 100-year time horizon were considered: 27.2 for methane and 273 for nitrous oxide. The functional unit was defined as 1 kg fat and protein-corrected milk (FPCM). The biophysical allocation approach from the IDF Global Carbon Footprint Standard for the Dairy Sector 2022 was used. Data were gathered through a semi-structured survey conducted across 96 small-scale dairy farms in Nandi and Uasin Gishu Counties. Annual on-farm and off-farm emissions were estimated using the 2019 Refinement to the 2006 IPCC guidelines, databases, and local emission factors. In each farm, 6 scenarios were modeled as mitigation strategies: (S1) Improved feeding combined with a 10% increase in milk productivity; (S2) Improved feeding combined with a 20% increase in milk productivity; (S3) Improved feeding combined with a 30% increase in milk productivity; (S4) Removal of males from the herd combined with improved feeding and a 10% increase in milk productivity; (S5) Removal of males from the herd combined with improved feeding and a 20% increase in milk productivity; (S6) Removal of males from the herd combined with improved feeding and a 30% increase in milk productivity. In the improved feeding intervention, natural pasture intake was reduced by 50%, and replaced with Brachiaria Mulato II for its superior nutritional characteristics. On average, milk CF was 3.0 and 2.6 kgCO2eq kgFPCM-1 in Nandi and Uasin Gishu, respectively. CF reductions for each intervention scenario in both counties were as follows: (S1) 14 and 15%; (S2) 20 and 21%; (S3) 25 and 26%; (S4) 21 and 22%; (S5) 26 and 27%; and (S7) 31%. To conclude, milk CF reductions are achievable through measures like enhancing diet quality, increasing milk yields, and culling unproductive male animals from the herd.